Maryville, Mo., Rev. Ordinances no. 16, §§ 44-45 (1903) - (:unkn) unknown (My University, 1903)
Laws that prohibit carrying concealed weapons, bringing weapons to certain places, and selling weapons to minors, Revised Ordinance No. 16, §§ 44-45: If any person shall carry concealed, upon or about his person, any deadly or dangerous weapon, or shall go into any church or place where people are assembled for religious worship, or into any school room or place where people are assembled for educational, literary or social purpose, or to any election precinct on any election day, or into any court room during the sitting of court, or into any other public assemblage of persons met for any lawful purpose other than for militia drill or meetings called under the militia law of this state, having upon or about his person any kind of fire-arms, bowie knife, dirk, dagger, slung-shot or other deadly weapon, or shall in the presence of one or more persons exhibit any such weapon in a rude, angry or threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated or under the influence of intoxicating drinks, or shall directly or indirectly sell or deliver, loan or barter to any minor any such weapon, without the consent of the parent or guardian of such minor, he shall be deemed guilty of a misdemeanor and upon conviction thereof be fined not less than ten nor more than one hundred dollars.
Keywords: BRANDISHING; CARRY - CONCEALED; SENSITIVE PLACES; TRANSFER - MINORS